The new coronavirus disease: what do we know so far?. (2nd May 2020) - Tang, Sammer; Brady, Mike; Mildenhall, Jo; Rolfe, Ursula; Bowles, Alexandra; Morgan, Kirsty
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus that causes the new disease COVID-19. Symptoms range from mild to severe with a higher incidence of severe cases in patients with risk factors such as older age and comorbidities. COVID-19 is mainly spread through the inhalation of respiratory droplets from coughing or sneezing or via contact with droplet-contaminated surfaces. Paramedics should be aware that some aerosol-generating procedures may put them at a higher risk of contracting the virus via possible airborne transmission. Use of remote triage clinical assessment is likely to increase as a result of the pandemic. There is no curative drug treatment for the virus and some medications may exacerbate its effects or make patients more susceptible to it. Evidence and guidelines are evolving on SARS-CoV-2 and COVID-19. Paramedics should keep up to date with the latest clinical guidance from their employers.